THE IMPACT OF CASH TANSFER ON FAMILY’S ATTITUDE AND COPYING MECANISM - Lilis Sulastri; Moh. Dulkiah (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2017)
The article studies the Impact of Cash Transfer on Family’s attitude and Social-Economy Development. The methodology of this study is mix methodology. Theoritical framework of this study is new institutionalism. The exercise field of this study is receiver of cash transfer in West Java and Bali. The paradigm of this research is departed from social fact and verstehen as the way of understanding and appreciation of a phenomenon socially, culturally, and economy in a deep consideration. A discourse on ideal type concept is a part of the study on ‘objectivity’ in the social scientific world. Ideal type conception directs a sociologist in developing his/her capability through guidelines to construct a hypothesis. Ideal type is hint a picture of reality but more to the aim of describing an ambiguous ‘means of expression’ in the picture. Empirical research attempts to comprehend a social phenomenon placing the observed events or actions with one or more ideal types. This study finds that capital, especialy social and economic capital, would be main key of cash transfer for success maintaining and developing societies. Quantity and Quality of capital decide opportunity for success and reward (trust) which is received. In other side, the form of Cash Transfer in economic action is mutual effect. Institutionalization of cash trasfer governance will impact on family’s attitude and copyng mecanism.